2017
DOI: 10.25181/jppt.v17i2.292
|View full text |Cite
|
Sign up to set email alerts
|

Uji Ketahanan Planlet Anggrek Bulan (Phalaenopsis amabilis (L.) Bl.) Hasil Seleksi dengan Asam Salisilat Terhadap Fusarium oxysporum Secara In Vitro

Abstract: Phalaenopsis amabilis cultivated have many constraints such as the appearance of fusarium wilt disease caused by Fusarium oxysporum. Plantlet P.amabilis which resistant to F. Oxysporum was selected in the solid Vacin and Went (VW) medium was added with salicylic acid at concentrations of 65 ppm, 75 ppm, and 85 ppm, compared with controls (0 ppm). The goals of the research were to study and determine of: 1) The SA concentration of planlet P. amabilis selection tolerant; 2) The proper concentration of AS during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…The research results of Rasmani et al (2020) showed that 40 mgL -1 fusaric acid was the optimal concentration for in vitro selection of Phalaenopsis amabilis (moon orchid) orchids. In general, in several in vitro selection studies on fusarium, it is known that the best concentrations of fusaric acid range from 30-45 mgL -1 (Damayanti et al, 2022;Damayanti, 2004;Noviantia et al, 2017). This concentration was able to induce resistance in banana plants.…”
Section: Effect Of Gamma Irradiation On Shoot Regenerationmentioning
confidence: 99%
“…The research results of Rasmani et al (2020) showed that 40 mgL -1 fusaric acid was the optimal concentration for in vitro selection of Phalaenopsis amabilis (moon orchid) orchids. In general, in several in vitro selection studies on fusarium, it is known that the best concentrations of fusaric acid range from 30-45 mgL -1 (Damayanti et al, 2022;Damayanti, 2004;Noviantia et al, 2017). This concentration was able to induce resistance in banana plants.…”
Section: Effect Of Gamma Irradiation On Shoot Regenerationmentioning
confidence: 99%
“…Jendoubi et al (2015) melaporkan bahwa pemberian asam salisilat 200 μM terbukti aman dan dapat meningkatkan ketahanan tanaman tomat terhadap Fusarium oxysporum f.sp radicis lycopercisi. Sementara Noviantia et al (2017) melaporkan bahwa konsentrasi asam salisilat 85 ppm secara in vitro efektif menekan perkembangan penyebab penyakit layu yang disebabkan oleh Fusarium oxysporum pada anggrek P. amabilis. Namun belum diketahui apakah planlet in vitro P. amabilis dapat diinduksi ketahanannya terhadap D. dadantii dengan asam salisilat.…”
Section: Pendahuluanunclassified
“…Orchids are ornamental plants that have the potential to be developed due to their economic value with a variety of shapes, colors, sizes, distinctive aromas, long-lasting quality of flowers, in addition to their potential as medicinal plants, cut flowers and potted plants. Orchids consist of 800 genera and 25,000 species [1], one of them is Dendrobium. Dendrobium is one of the largest orchid genera in the Orchidaceae family, and includes more than 2,000 species.…”
Section: Introductionmentioning
confidence: 99%